Bacterial Autoinducer Derived 4-Quinolones as Novel Immune Modulators - Purcell, Ian Charles (2007)
Immunological disorders, including those of an autoimmune nature, cause chronic morbidity and disability. These conditions are not well controlled with current therapies and issues, including the lack of specificity of action, lead to a number of adverse drug effects. Thus the search for alternative immune modulating agents is a well sought after objective.